Leg Paralysis Inducement by Risella 17 Oil in Lucilia sericata (Meig) as Affected by Sex, Time, Application Site, and oil Volume1 - Lim, G. S. (1978)
Development of leg paralysis induced by Risella 17 oil on Lucilia sericata (Meig.) was found to be significantly affected by sex, time, application site, and oil volume. Male flies were noted to be mrJre susceptible than female flies. In both sexes, more were affected at a given time when a greater volume of oil was applied. The PVso (volume of oil required to induce paralytic symptoms in 50% of the treated flies) was found to be 0.13 p.l for the male flies, and 0.2 /l-l for the female flies. Their probit regression lines are: y = 4.01x + 0.57 for the male, and y = 2.64x +1 .35 for the female. The number of male flies that developed leg paralysis was dependent on the site of application. With 0.3 p. I of oil, there were about twice as many flies affected in treatment on the abdomen as compared to that on the thorax. However, no significant difference was observed between applications made dorsally and ventrally on the abdomen. Flies treated on the head and legs did not develop any paralytic symptoms. The findings suggest that there is more than one mode of action. However, the relative importance and role of any mode of action in contributing to the paralysis inducement with subsequent death, would require further and more critical investigations.